Impella versus extracorporal life support in cardiogenic shock: a propensity score adjusted analysis. (9th February 2021) - Wernly, Bernhard; Karami, Mina; Engström, Annemarie E.; Windecker, Stephan; Hunziker, Lukas; Lüscher, Thomas F.; Henriques, Jose P.; Ferrari, Markus W.; Binnebößel, Stephan; Masyuk, Maryna; Niederseer, David; Abel, Peter; et al.
Abstract: Aims: The mortality in cardiogenic shock (CS) is high. The role of specific mechanical circulatory support (MCS) systems is unclear. We aimed to compare patients receiving Impella versus ECLS (extracorporal life support) with regard to baseline characteristics, feasibility, and outcomes in CS. Methods and results: This is a retrospective cohort study including CS patients over 18 years with a complete follow‐up of the primary endpoint and available baseline lactate level, receiving haemodynamic support either by Impella 2.5 or ECLS from two European registries. The decision for device implementation was made at the discretion of the treating physician. The primary endpoint of this study was all‐cause mortality at 30 days. A propensity score for the use of Impella was calculated, and multivariable logistic regression was used to obtain adjusted odds ratios (aOR). In total, 149 patients were included, receiving either Impella ( n  = 73) or ECLS ( n  = 76) for CS. The feasibility of device implantation was high (87%) and similar (aOR: 3.14; 95% CI: 0.18–56.50; P  = 0.41) with both systems. The rates of vascular injuries (aOR: 0.95; 95% CI: 0.10–3.50; P  = 0.56) and bleedings requiring transfusions (aOR: 0.44; 95% CI: 0.09–2.10; P  = 0.29) were similar in ECLS patients and Impella patients. The use of Impella or ECLS was not associated with increased odds of mortality (aOR: 4.19; 95% CI: 0.53–33.25; P  = 0.17), after correction for propensity score and baseline lactate level. Baseline lactate level was independently associated with increased odds of 30 day mortality (per mmol/L increase; OR: 1.29; 95% CI: 1.14–1.45; P  < 0.001). Conclusions: In CS patients, the adjusted mortality rates of both ECLS and Impella were high and similar. The baseline lactate level was a potent predictor of mortality and could play a role in patient selection for therapy in future studies. In patients with profound CS, the type of device is likely to be less important compared with other parameters including non‐cardiac and neurological factors.